Examining Work Group Functioning and Occupational Stress on Turnover Intention among Academic and Non-Academic Staff in Nigeria - Ibini, Olabode; Nwaizugbe, Samuel; Ajisebiolowo, Samson; Uye, Emmanuel (Universitas Nurul Jadid, 2025)
Turnover intention has remained an emerging issue in university system every year in Nigeria. As the university system continue to experience increasing number of staff turnover, investigating some of the predictors of turnover intention become imperative. Therefore, this study examines the predictive ability of work group functioning and occupational stress on turnover among academic and non-academic staff in a Nigerian university. Cross-sectional design was utilized while purposive sampling technique was used to select the study population. Social Exchange Theory anchored the study. Data were collected from 250 academic and non-academic staff of the Alex Ekwueme Federal University, Ndufu-Alike Ikwo using validated scales. Data collected were analysed using hierarchical multiple regression to test hypothesis that was accepted at p < .001 level of significance. The result indicated that work group functioning and occupational stress were statistically significant predictors of turnover intention among study participants. In addition, work group functioning and occupational stress were statistically significant independently predictors of turnover intention among study participants. The study concludes that work group functioning and occupational stress are marginally contributed to turnover intention among study participants. The study recommends that the Nigerian university HR strategies should include putting in place an enabling work environment that reduces stress and turnover intention.